Denture bar-coding: An innovative technique in forensic dentistry - Dineshshankar, Janardhanam (J Pharm Bioallied Sci, 2015)
Denture markers play an important role in forensic odontology and also in identifying a person. A number of methods are there for identifying dentures from a less expensive technique to a more expensive technique. Out of different denture markers, the bar-coding system is a way of collecting data from the mobile. Even a huge amount of data can be stored in that. It can be easily incorporated during acrylization of the denture and thus could be helpful in identification. This article reviews the strengths of bar-coding and how easily it can be used in the routine procedure.